Rousseau i nowożytne spotkanie z Innym - Sylwester Zielka (Problemy Wczesnej Edukacji, 2015)
The paper situates the thought of Jean Jacques Rousseau in the context of the 17th and 18th century social and political debate on the possibility of creating a better society, which intensified with the crisis of feudal system and early modern discovery of the Other. The paper also discusses consequences of this debate for shaping anthropology as a field of knowledge and understanding culture of the time. The idea of a “noble savage” according to which non-Europeans, i.e., the “primitive” people living in the state of nature as free and equal, without concerns and inconveniences of civilization, is contrasted with an opposite project of a “degenerate savage” of Thomas Hobbes, who used it as a justification for absolute monarchy in European countries and of European societies over non-Western ones.